Student Creativity in Developing Interactive Multimedia Using Kodular for Junior High School Mathematics Learning - Ummah, Siti Khoiruli; Azmi, Rizal Dian (Mathematics Education Journal, 2024)
This research is qualitative research that aimed to investigate the results of the development of learning media by students to improve school students' creative performance and students' creative thinking using the Kodular application. This study focuses on the problem of the lack of learning media at the junior high school level which is used as a means of independent learning for students at home. The subject was a class of The Department of Mathematics Education. The research subjects were 41 students in the department of mathematics education. data were taken using observation and documentation techniques that were adapted to mathematical creative thinking indicators. Interactive multimedia developed by students in the form of mathematical material presented in text form, containing equations, screenshots of graphics from the Desmos application, and video explanations of the material. Furthermore, practice questions and post-tests are presented using the help of Google Form, Quizziz, and Liveworksheets so that users get a direct response to the answers to the questions so that they meet the interactive characteristics of the learning media. The results obtained are 41 students are able to develop interactive multimedia that is run through an android application in junior high school mathematics learning. Creative thinking skills are achieved by using the dimensions of fluency, flexibility, and originality. This is achieved from media development carried out by students The creative performance of students reaches the usefulness dimension but has not been able to reach the novelty of the interactive multimedia that has been developed.